Penelitian Pembuatan formulasi Pestisida Bentuk Pekatan Yang Dapat Diemulsikan (EC) - Hendartini Hendartini (Balai Besar Kimia dan Kemasan, 1989)
One of the most important and widely used types of pesticide formulation is Emulsifiable Concentrate, abbreviated as EC. An EC formulation can be defined as non=aqueoussolution of a pesticideactive ingredient and emulsifiers in a suitable solvent. In this experiment 4 types of BPMC Emulsifiable Concentrate formulation were prepared at various emulsifier types and concentrations. Agrisol emulsifier was used for control.The new formulations which have been prepared give a bit lower physico chemical test result, compared with the agrisol formulation especially in 8% and 10% concentration that fulfil the SII requirements.